Ensuring the Rights of Indigenous Peoples: International Legal Standards and National Implementation - Gusniarjo Mokodompit; Suprijati Sarib; Sabil Mokodenseho; Zulfikri Darwis; Madinah Mokobombang (Eastasouth Institute, 2023)
This research explores the guarantee of indigenous peoples' rights in indigenous territories in West Java, focusing on international legal standards and their implementation at the national level. The research used a mixed-methods approach, combining qualitative and quantitative methods. Through document analysis, surveys and interviews with key stakeholders, the research examines the legal and policy framework, challenges and opportunities related to indigenous peoples' rights in the region. The findings highlight issues such as land rights, cultural preservation, and political participation. While there are legal provisions in place, their practical implementation faces challenges such as conflicting land tenure systems, limited recognition of customary land rights, and lack of consultation and participation of indigenous peoples. This research emphasizes the need for effective implementation of international legal standards, capacity building, and empowerment of indigenous peoples. The findings contribute to the understanding of indigenous peoples' rights in West Java and provide insights for policy makers, indigenous peoples, and other stakeholders involved in protecting indigenous peoples' rights.